SCD1 licenses STING signaling through fatty acid desaturation–mediated membrane remodeling - Danhui Qin; Yanjie Gao; Haojia Jiang; Xintong Meng; Ying Qin; Hui Song; Yue Fu; Chengjiang Gao; Mutian Jia; Chunyuan Zhao; Wei Zhao (Proceedings of the National Academy of Sciences, 2026)
The stimulator of interferon genes (STING) is a critical mediator of innate immunity against cytosolic DNA pathogens, requiring precise regulation to balance antiviral defense and immune tolerance. While lipid metabolism influences immune signaling, the role of stearoyl-CoA desaturase 1 (SCD1), a key enzyme converting saturated fatty acids (SFAs) to monounsaturated fatty acids (MUFAs), in STING activation remains unexplored. Here, we identify SCD1 as a metabolic checkpoint that licenses STING activation through biophysical membrane remodeling. Mechanistically, SCD1-generated MUFAs incorporate into endoplasmic reticulum (ER) phospholipids, enhancing membrane curvature and fluidity. This biophysical remodeling facilitates cyclic guanosine monophosphate (GMP)-adenosine monophosphate (AMP) (cGAMP) binding to STING and promotes its dimerization, enabling downstream TBK1-IRF3 signaling and type I interferons (IFNs) production. Consequently, Scd1 deficiency or pharmacological inhibition impairs STING activation, attenuates antiviral responses against herpes simplex virus-1 (HSV-1), and exacerbates viral replication in vitro and in vivo. Conversely, MUFAs supplementation rescues STING activation in Scd1 -deficient models. Our findings establish SCD1-mediated lipid desaturation as a fundamental regulator of STING-driven immunity, highlighting its therapeutic potential for disorders of aberrant STING activation.